Exploring Code Mixing in EFL Teaching and Learning Contexts: A Qualitative Study at SMAN 9 Cirebon: Mengeksplorasi Campur Kode dalam Konteks Pengajaran dan Pembelajaran Bahasa Inggris: Sebuah Studi Kualitatif di SMAN 9 Cirebon - Marcha, Famela; Darma, Virga Putra; Nopiyadi, Dwi (NextGen Education Review Journal, 2025)
Code mixing has become a common tendency among society. This research was conducted to explore all the types of code mixing utilized by EFL teachers of SMAN 9 Cirebon and find out the dominant type. This research also aims to determine the specific context and the purposes of EFL teachers utilizing code mixing in the teaching and learning process. Purposive sampling was used to take the subject. Two EFL teachers were the subjects of this research and the object of this research was the code mixing utilized by these teachers in their teaching and learning. In gathering the data, the researcher used observations and interviews. This research used the theory of Muysken (2005) to analyze the types of code mixing utilized by EFL teachers of SMAN 9 Cirebon. The findings revealed that code mixing remains prevalent at the senior high school level. Among the EFL teachers at SMAN 9 Cirebon, the types of code mixing identified in their teaching and learning contexts include insertion, alternation, and also congruent lexicalization; in which insertion emerged as the dominant type of code mixing utilized by EFL teachers at SMAN 9 Cirebon. EFL teachers utilized code mixing in the teaching and learning to ensure effective learning, proper achievement of learning objectives, and enhanced student comprehension. Overall, code mixing is still necessary at the senior high school level to support effective learning and achieve learning objectives.